2019
DOI: 10.1021/acs.jpca.9b05549
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Diiodine with Heteroaromatic N-Oxides: Effects of Halogen-Bond Acceptors in Halogen Bonding

Abstract: Halogen bonding (XB) in complexes of diiodine with heteroaromatic N-oxides was examined via a combination of UV–vis spectral and X-ray structural measurements, as well as computational analysis. While all of these associates were formed by analogous I···O bonds, they showed considerable variations of formation constants (5–1500 M–1) and intermolecular I···O bond length (2.3–3.2 Å). In the solid state, both atoms of I2 molecules were involved in XB, and the I···O separations were determined by the electron-dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Figure 3 shows that all Cl-I covalent bonds are shorter than I-I bonds by at least 0.15 Å and the Cl-I bonds in crystals have generally larger local stretching force constant values than I-I bonds although they overlap in the range of 0.95-1.35 mdyn/Å. All X-I covalent bonds in crystal models are longer and weaker than their molecular counterparts in gas phase, which is a result of delocalization of lone pair electrons into the σ * (X-I) anti-bonding orbital [97] upon halogen bonding in crystals. Furthermore, we found that when the halogen bond acceptor is an ether group (G, H, J, K) the X-I bond is stronger than those when halogen bonds have N-oxides (L, M, N, O, P, Q) as acceptors.…”
Section: Comparison Of Experimental and Calculated Structuresmentioning
confidence: 97%
See 3 more Smart Citations
“…Figure 3 shows that all Cl-I covalent bonds are shorter than I-I bonds by at least 0.15 Å and the Cl-I bonds in crystals have generally larger local stretching force constant values than I-I bonds although they overlap in the range of 0.95-1.35 mdyn/Å. All X-I covalent bonds in crystal models are longer and weaker than their molecular counterparts in gas phase, which is a result of delocalization of lone pair electrons into the σ * (X-I) anti-bonding orbital [97] upon halogen bonding in crystals. Furthermore, we found that when the halogen bond acceptor is an ether group (G, H, J, K) the X-I bond is stronger than those when halogen bonds have N-oxides (L, M, N, O, P, Q) as acceptors.…”
Section: Comparison Of Experimental and Calculated Structuresmentioning
confidence: 97%
“…with N-oxide acceptors via crystallography and theoretical calculations [96,97]. Their analysis based on molecular dimer models suggests that the charge transfer is a key factor in the I• • • O halogen bonding besides electrostatic attraction.…”
Section: Recently Rosokha and Co-workers Investigated The I-i• • • Omentioning
confidence: 99%
See 2 more Smart Citations
“…have shown using N‐iodosaccharin (NISac) and highly nucleophilic 4‐ N , N ‐dimethylaminopyridine (DMAP) as the XB acceptor, that the N−I bond of the N‐haloimide can be dissociated forming an iodo‐pyridinium cation and N‐saccharinate anion, that is, forming a salt . While strong XBs with N‐heterocycles are common, the development of (strong) halogen bonds using other Lewis bases for example, ( N ‐oxide) oxygen, has remained largely unexplored …”
Section: Introductionmentioning
confidence: 99%